Literasi Keuangan Syariah dan Perannya dalam Meningkatkan Kesejahteraan Masyarakat melalui Praktik Ekonomi Syariah - Pardan Syafrudin (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2026)
Islamic financial literacy plays a fundamental role in improving public understanding of financial principles based on Islamic law and encouraging the implementation of ethical economic practices. However, the level of public literacy regarding Islamic financial products and services remains relatively low, limiting the development of the halal economy and financial inclusion. This study aims to analyze the strategic role of Islamic financial literacy in enhancing public awareness, promoting responsible financial behavior, and supporting sustainable socio-economic welfare from an Islamic perspective. This research employs a qualitative approach using a literature review method by examining scholarly publications, regulatory frameworks, and relevant studies concerning Islamic financial literacy and the development of the halal economy. The findings indicate that Islamic financial literacy extends beyond understanding financial products to encompass comprehension of Islamic economic principles, including the prohibition of riba, gharar, and maysir, asset-backed financing, risk-sharing, and adherence to halal investment practices. Increased literacy contributes to more informed financial decision-making, broader utilization of Islamic financial institutions, and stronger support for the growth of halal industries, including halal tourism and other Sharia-based economic sectors. The study concludes that strengthening Islamic financial literacy is a strategic instrument for accelerating Islamic economic development, expanding financial inclusion, and promoting equitable and sustainable welfare (al-falah). Therefore, collaborative efforts among government institutions, educational organizations, Islamic financial institutions, and community stakeholders are essential to enhance public literacy and optimize the contribution of the Islamic financial ecosystem to national economic development.